Edukasi Asuransi sebagai Langkah Penguatan Ketahanan Keuangan Masyarakat Kolaborasi Fakultas Ekonomi dan Bisnis Universitas Brawijaya bersama PT Asuransi Umum Bumida 1976 Cabang Malang - A Muhamad Jazuli; Putu Prima Wulandari; Kitut Kitut; Nuraini Desty Nurmasari (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aims to strengthen financial literacy and insurance awareness among high school students and final-year university students in Malang through a collaboration between Universitas Brawijaya and PT Asuransi Umum Bumida 1976 Malang Branch. The program was implemented through three systematic stages: preparation (needs assessment and development of educational modules), implementation (knowledge transfer and financial attitude formation through interactive methods), and evaluation using pre-test and post-test instruments. A number of participants completed the entire program series. The results indicate an improvement in participants’ financial literacy based on comparisons between pre-test and post-test scores, as well as a significant shift in attitudes from skepticism to greater openness toward the utilization of insurance products.